Budidaya Maggot Black Soldier Fly untuk Pengolahan Sampah Organik bagi Warga Makamhaji, Sukoharjo: Cultivation of Black Soldier Fly Maggots for Organic Solid Waste Treatment for Makamhaji Residents, Sukoharjo - Purnama, Herry; Triyono, Agus; Kuswati, Rini; Hidayati, Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The solid waste problem is still a topic of discussion in various forums. One of the most densely populated villages in Sukoharjo Regency, i.e. Makamhaji Village, produces a large volume of waste, and is a problem in itself. This Community Service Program invites the people of Windan, Makamhaji to process household organic solid waste through maggot bioconversion which can also have economic value. The team carried out socialization and community empowerment activities to reduce the amount of waste through maggot cultivation which can decompose organic waste into protein as part of the life cycle of black soldier flies (BSF). This program aims to provide technological information in maggot cultivation and improve the quality of human resources. The methods applied are through training, mentoring, monitoring, evaluation, provision and lending of facilities, and increasing cooperation networks with business actors in the field of waste processing. Community service activities have succeeded in fostering residents to carry out maggot cultivation and are quite productive so that they can increase income.